Redefining respite for family caregivers: lessons learned from the COVID-19 pandemic - Utz, Rebecca L.; Mundinger, Hannah L.; Thompson, Amber; Towsley, Gail L.; Dassel, Kara B.; Terrill, Alex; Bristol, Alycia A. (Frontiers in Health Services, 2025)
IntroductionRespite care is provided to caregivers through in-home respite providers, drop-off day centers, and institutional or overnight facilities, where the caregiver can take a break or get time-away, while the care-recipient is provided with personal care, companionship, and/or supervision. During the global COVID-19 pandemic (2020+), these types of formal respite services were disrupted, leaving caregivers with little to no access to respite. This study aimed to understand how caregivers accessed and achieved respite when respite services were not readily available, and how their experiences during and following the unprecedented global public health crisis have influenced and informed the way that caregivers achieve the needed and desired respite.MethodsThis study integrates several sources of qualitative and descriptive data collected via electronic surveys and semi-structured interviews with family caregivers and respite providers over the past several years (from 2019 to 2024).ResultsThe following themes were identified: (a) disruption and loss of formal respite services resulted in caregiver isolation, as well as acute and protracted stress, (b) personal networks and shared caregiving arrangements provide opportunities for informal respite, (c) respite is associated improved caregiver wellbeing, but caregivers often are hesitant to use respite (d) daily activities and routines can provide a form of respite for caregivers, (e) family caregivers showed resilience and adaptability in the face of COVID-19 challenges, revealing the potential benefit of taking “short breaks” throughout the day to achieve a feeling of respite.Discussion and conclusionsThese qualitative, descriptive insights provide a blueprint for a reimagined definition of caregiver respite, where respite is conceptualized as an outcome or benefit that caregivers seek and can create on their own, rather than only defining respite as a formal service provided to caregivers by outside organizations. In the face of significant workforce shortages that threaten the widespread availability and access to formal respite services, a re-imagined model of respite has the potential to better meet the respite needs and wishes of family caregivers, and maximize the benefit of short-breaks when formal respite services may not be available.